Studies on Effect of Age of Seedling and Levels of Nitrogen on Performance of Hybrid Rice (Oryza sativa L.) - Kumar, Govinda; Acharya, Shivasankar; Pathak, S. K.; Kumar, Sunil; Homa, Fozia; Kumar, Arun (International Journal of Bio-resource and Stress Management, 2019)
A field experiment was conducted during kharif season of 2018 at Bihar Agricultural College Farm, Sabour, Bhagalpur, Bihar, to study the effect of age of seedling and levels of nitrogen on performance of hybrid rice (Oryza sativa L.) variety Arize-6444 Gold. The experiment was laid out in a split-plot design, replicated thrice with main plot assigned to three levels of age of seedling and subplot with four nitrogen levels. The result revealed highest grain yield (5374 kg ha-1) recorded with 15 days seedling, being at par with 20 days seedling (5216 kg ha-1), but differed significantly with 25 days seedling (4934 kg ha-1). Among the nitrogen levels, significant difference in grain yield and harvest index was found with 150 kg N ha-1 with values of 6050 kg ha-1 and 45.21% respectively, being at par with 180 kg N ha-1, whereas the highest straw yield (7439 kg ha-1) was recorded with 180 kg N ha-1, being at par with 150 kg N ha-1.The highest net return(Rs. 60,850 ha-1)was obtained with 15 days seedling, which was found at par with 20 days but differed significantly from 25 days seedling. Nitrogen levels significantly influenced the net return and B:C ratio, with the highest net return (Rs.73014 ha-1)and B:C ratio (1.67) obtained with 150 kg N ha-1 respectively, being at par with 180 kg N ha-1 with net return and B:C ratio of Rs. 69,139 ha-1 and 1.56 respectively, differing significantly from 120 kg N ha-1 and no nitrogen plot.